Social patterns underlying a new group formation in olive baboons - Jacob A. Feder; Shirley C. Strum; Joan B. Silk (PLoS ONE, 2025)
In group-living animals, social and ecological challenges can push groups to fission into two or more ‘daughter’ groups. Here, we describe the demographic and social behavioral changes that were associated with the formation of a new group of olive baboons ( Papio anubis ) in Laikipia, Kenya. The process began when a high-ranking natal male transferred into a nearby study group, which coincided with the dispersal of several adult females. The dispersing females had close social ties with this male, and he had sired most of their current offspring. After a stint in the neighboring group, these animals eventually budded off to form a new, separate group. Throughout the fission process, female-female grooming was strongly predicted by eventual fission outcomes. In other words, females groomed most with the females they would remain with after the fission. By contrast, female-male grooming was prevalent in co-resident dyads but less strictly predicted by eventual fission outcomes. Although rates of aggression were elevated during periods when females dispersed, females who moved between groups were not targeted for eviction. Intergroup grooming remained elevated throughout the fission process, particularly between mixed-sex dyads, suggesting that group boundaries may have remained somewhat blurred. Taken together, the formation of this new group appears to have been a product of social factors including elevated levels of female-female aggression and females’ affinity for particular males.